A PRELIMINARY EXAMINATION OF THE MEANING AND EFFECT OF LIMITED LITERACY IN THE LIVES OF PEOPLE WITH SERIOUS MENTAL ILLNESS. Issue 3 (April 2015) - Lincoln, Alisa K.; Arford, Tammi; Doran, Meghan V.; Guyer, Margaret; Hopper, Kim
<x xml:space="preserve">Abstract</x> The relationship between literacy and health has been well documented: research shows that people with limited literacy skills have worse health outcomes for numerous chronic conditions. However, little is known about how literacy relates to mental health, including access to treatment and recovery. A pilot study was conducted with mental health services users with varying literacy skills at two urban, public mental health clinics to more fully understand how literacy affects the lives of people living with serious mental illness. The study was designed using a Community‐Based Participatory Research approach; mental health service users informed the development of the interview guide. Findings demonstrate that those with limited literacy skills experience increased stigma, have fewer options for accessing information about conditions and treatment plans, and may be excluded from certain cognitive‐behavioral treatments that require basic literacy skills. These barriers can significantly affect service utilization and mental health outcomes.